Gender-specific association of loneliness and health care use in community-dwelling older adults - Böhlen, Friederike; Heider, Dirk; Schellberg, Dieter; Hohls, Johanna Katharina; Schöttker, Ben; Brenner, Hermann; Friederich, Hans-Christoph; König, Hans-Helmut; Wild, Beate (BMC geriatrics, 2023)
Loneliness in older adults is common, particularly in women. In this article, gender differences in the association of loneliness and health care use are investigated in a large sample of community-dwelling older adults.